2015
DOI: 10.1007/s12062-015-9132-0
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to Well-Being in Later Life: Socioeconomic and Health Determinants Across the Life Course of Australian Baby Boomers

Abstract: In many countries like Australia and the United States, baby boomers are referred to as the ‘lucky cohort’, yet there has been little research on the origins and extent of inequalities within this cohort. This study uses path analysis to investigate direct and indirect effects of childhood and adult socioeconomic status and health on two subjective well-being measures: quality of life and life satisfaction. Retrospective life course data were obtained for 1,261 people aged 60 to 64 in the 2011–12 Life Historie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 70 publications
3
30
0
2
Order By: Relevance
“…Previous studies have shown inconsistencies in the association between childhood SEP and adult mental wellbeing [ 10 , 11 , 12 , 13 , 15 , 16 ], which could have been due to modification of this association by country, cohort or age, or because of the different measures of wellbeing and SEP utilised. Our findings used harmonised data on the wellbeing outcome and the SEP exposures and yet we still found differences across these four studies set in Britain, which is suggestive of cohort or age differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown inconsistencies in the association between childhood SEP and adult mental wellbeing [ 10 , 11 , 12 , 13 , 15 , 16 ], which could have been due to modification of this association by country, cohort or age, or because of the different measures of wellbeing and SEP utilised. Our findings used harmonised data on the wellbeing outcome and the SEP exposures and yet we still found differences across these four studies set in Britain, which is suggestive of cohort or age differences.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies, both using data from the Survey of Health, Ageing and Retirement (SHARE), found an association between more disadvantaged childhood SEP and lower life satisfaction at older ages (50 years and older) that persisted after adjusting for adult circumstances, such as education, income, employment and partnership status [ 10 ] [ 11 ]. One study of Australian baby-boomers in the early sixties [ 12 ] and one of people in their mid-30s living in Britain [ 13 ] have found that the association between childhood SEP and adult wellbeing was fully attenuated by adjustment for adult SEP, thus suggesting that socioeconomic disadvantage in childhood sets the course for a disadvantaged trajectory during adulthood which can then affect wellbeing [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Positive parenting in early childhood is associated with better quality adult relationships for their offspring, 13 31 better adult socioeconomic position (SEP) 32 and lower risk of adult mental disorder 33 all of which are associated with adult mental well-being. 34 35 Parental mental ill health was also independently associated with poorer adult mental well-being. One possible explanatory pathway is through childhood and adolescent mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Childhood socio-economic position (SEP), as distinct from specific adversities, is also associated with later-life depression. Again, some studies suggest lasting direct effects (Luo and Waite 2005;Schaan 2014) whereas others indicate that associations are mediated by educational attainment, adult SEP, and adult social resources (Nicholson et al 2008;Kamiya et al 2013;Kendig et al 2015).…”
Section: Theoretical Backgroundmentioning
confidence: 99%